Evaluating the Implementation of the Sekolah Penggerak Policy In Cianjur, Indonesia: Addressing Challenges And Enhancing Outcomes - Ruhimat, Mochammad Devi Cahya; Rahyasih, Yayah; Shodikin, Rifan (AL-ISHLAH: Jurnal Pendidikan, 2024)
The Program Sekolah Penggerak (PSP) is a priority initiative launched by Indonesia’s Ministry of Education, Culture, Research, and Technology (Kemendikbud) to drive rapid school transformation and foster collaboration within the educational ecosystem at the regional level. Despite these efforts, 2,504 schools in the first cohort of the program were deemed unsuccessful after three years of receiving targeted support and funding. This study aims to assess the implementation of the PSP Batch 2, which has been operational for over two years in Cianjur Regency, Indonesia, through a retrospective analysis. The findings are critical for formulating policy recommendations to address the weaknesses identified in the implementation process. A descriptive qualitative case study approach was employed, utilizing snowball sampling for data collection and analysis. The results provide insights into (1) the chronology of PSP Batch 2’s implementation in Cianjur Regency, (2) policy violations and challenges, including the lack of supporting local policies and frequent changes in school leadership during ongoing mentorship, and (3) recommendations for future PSP implementations, offering three key alternatives: centralization of the program, enhanced inter-ministerial collaboration, and the development of region-specific policies. This study presents valuable guidance for policymakers in decentralized education systems and calls for further research in other regions to evaluate the PSP’s implementation mechanisms.